Reduced levels of stromal sex hormone-binding globulin and androgen receptor dysfunction in the sperm storage region of the rat epididymis - Santi, Fabiane de; Beltrame, Flavia L.; Hinton, Barry T.; Cerri, Paulo S. [UNESP]; Sasso-Cerri, Estela [UNESP] (Bioscientifica Ltd, 2018)
The cauda epididymidis is the major sperm storage region whose androgenic supply, essential for the sperm viability, is provided by the vasculature and is dependent upon testosterone diffusion through the stromal tissue to reach the epithelial cells. We have focused our efforts on examining the regulation of this important epididymal region by evaluating the impact of the androgen disrupter cimetidine on the epithelial-stromal androgenic microenvironment. Male rats received 100 mg/kg cimetidine (CMTG) or saline (CG) for 50 days, serum testosterone levels were measured and the epididymal cauda region was processed for light and transmission electron microscopy. In the proximal cauda region, the duct diameter was measured and birefringent collagen in the stroma was quantified. TUNEL-labeled epithelial cells were quantified, and androgen receptor (AR), karyopherin alpha (KPNA) and sex hormone-binding globulin (SHBG) levels were analyzed by immunofluorescence and Western blot. CMTG showed reduced duct diameter and high number of apoptotic epithelial cells. In the epithelium, the total AR concentration and the KPNA immunoreactivity were reduced, and a weak/absent AR nuclear immunofluorescence was observed in contrast to the enhanced AR immunolabeling observed in the cytoplasm of the epithelial cells. A significant reduction of collagen and SHBG levels in the stroma was also observed. Cimetidine treatment impairs AR nuclear import in the epithelium, causing androgenic dysfunction and subsequent epithelial cell apoptosis and duct atrophy. The connective tissue atrophy and reduction of SHBG stromal levels associated with epithelial androgenic dysfunction indicate a possible role of stromal SHBG in the androgenic supply of the sperm storage region of the epididymis.